Exploiting venom toxins in paratransgenesis to prevent mosquito-borne disease - Stephanie French; Rachael Da Silva; Janet Storm; Christida E. Wastika; India Cullen; Martijn ten Have; Grant L. Hughes; Cassandra M. Modahl (Parasites & Vectors)
Abstract Mosquitoes are responsible for the transmission of numerous pathogens, including Plasmodium parasites, arboviruses and filarial worms. They pose a significant risk to public health with over 200 million cases of malaria per annum and approximately 4 billion people at risk of arthropod-borne viruses (arboviruses). Mosquito populations are geographically expanding into temperate regions and their distribution is predicted to continue increasing. Mosquito symbionts, including fungi, bacteria and viruses, have desirable traits for mosquito disease control including spreading horizontally and vertically through mosquito populations and potentially colonising multiple important vector species. Paratransgenesis, genetic modification of mosquito symbionts with effectors to target the pathogen rather than the vector, is a promising strategy to prevent the spread of mosquito-borne diseases. A variety of effectors can be expressed but venom toxins are excellent effector candidates because they are target specific, potent and stable. However, the only toxins to be explored in mosquito paratransgenesis to date are scorpine and mutated phospholipase A2. To enhance the scope, effectiveness and durability of paratransgenesis, an expanded arsenal of effectors is required. This review discusses other potential toxin effectors for future paratransgenesis studies based on prior in vitro and in vivo antiparasitic and antiviral studies and highlights the need for further research and investment in this area. In terms of mosquito-borne diseases, paratransgenesis strategies have been developed to target Plasmodium. We postulate the potential to apply this principle to target arboviruses using antiviral toxin effectors. Graphical Abstract